Announcement — The Paper Award of Tribology Online – - Masabumi Masuko (Japanese Society of Tribologists, 2014)
The Japanese Society of Tribologists is pleased to announce that the 2013 Paper Award of Tribology Online was awarded to:“Effect of Environmental Gas on Surface Initiated Rolling Contact Fatigue,” by Hiroyoshi Tanaka, Tatsuhiko Morofuji, Kakeru Enami, Masaaki Hashimoto, Joichi Enami, Vol. 8, No. 1(2013) 90-96.and“Effects of Surface Chemical Properties on the Frictional Properties of Self-Assembled Monolayers Lubricated with Oleic Acid,” by Koji Miyake, Takamasa Kume, Miki Nakano, Atsushi Korenaga, Koji Takiwatari, Ryo Tsuboi, Shinya Sasaki, Vol. 7, No. 4 (2012) 218-224.The Award Medals were presented to the authors by Prof. Masabumi Masuko, the President of the Japanese Society of Tribologists, at the JAST Annual Meeting on 20th May, 2014.The Paper Award of Tribology Online is given annually to the author(s), either the JAST members or non-members, of the paper(s) judged as the best paper(s) published in Tribology Online (TROL) for the previous three years. All papers that appeared in TROL for the three years are reviewed by the JAST Awards Committee.